Strengthening Teacher Work Culture through Positive Discipline Strategy at SD Negeri 004 Balikpapan City - Arumwati; Dwi Sulisworo; Muhammad Zuhaery (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study aims to describe strategies for strengthening positive discipline in improving teachers’ work culture at SD Negeri 004 Balikpapan City. A qualitative approach with a case study design was employed. The participants consisted of the vice principal and teachers selected through purposive sampling. Data were collected through interviews, observations, and documentation, and analyzed using an interactive model of data reduction, data display, and conclusion drawing. The findings reveal that positive discipline is implemented through leadership role modeling, continuous supervision, effective communication, habituation of a positive work culture, and teachers’ professional development programs. These strategies contribute to improving teachers’ motivation, professionalism, collaboration, and sense of responsibility in performing their duties. Although several challenges were identified, including resistance to change among some teachers and high administrative workloads, the school consistently implemented guidance and strengthened internal communication to support improvement. Overall, the study concludes that positive discipline is an effective managerial strategy for fostering a professional, collaborative, and conducive teacher work culture in elementary schools.